Absolute Configuration of Oplopanone Derivatives From Serphidium stenocephalum: ECD Spectra of Acyclic Ketones With Front‐Octant Contributions. Issue 1 (19th November 2013) - Shafiq, Nusrat; Saleem, Muhammad; Riaz, Naheed; Tousif, Muhammad Imran; Jabbar, Abdul; Tareen, Rasool Bakhsh; Pescitelli, Gennaro
ABSTRACT The electronic circular dichroism (ECD) spectra of two sesquiterpenoids (1 and 2) related to oplopanone, obtained from a methanolic extract of the plant Serphidium stenocephalum (Artemisia stenocephala), were measured and reproduced by means of time‐dependent density functional theory (TDDFT) calculations, establishing their absolute configuration. The application of ketone octant rule for carbonyl n‐π* ECD band to compounds 1 and 2, which include an acyclic carbonyl group, was critically assessed. The peculiar oplopanone skeleton makes a straightforward application of the octant rule impossible, because of the uncertainty related to the shape of the so‐called third nodal surface separating front and back octants. The various group contributions to the carbonyl n‐π* ECD band were estimated with TDDFT calculations on selected molecular models obtained by consecutive dissections from 1. Chirality 26:39–43, 2013 © 2013 Wiley Periodicals, Inc.